Crossing limit cycles in piecewise smooth Kolmogorov systems: An application to Palomba's model - Carvalho, Yagor Romano; Gouveia, Luiz F.S. [UNESP]; Makarenkov, Oleg (Elsevier, 2025)
In this paper, we study the number of isolated crossing periodic orbits, so-called crossing limit cycles, for a class of piecewise smooth Kolmogorov systems defined in two zones separated by a straight line. In particular, we study the number of crossing limit cycles of small amplitude. They are all nested and surround one equilibrium point or a sliding segment. We denote by MpKc(n) the maximum number of crossing limit cycles bifurcating from the equilibrium point via a degenerate Hopf bifurcation for a piecewise smooth Kolmogorov systems of degree n=m+1. We make a progress towards the determination of the lower bounds MKp(n) of crossing limit cycles bifurcating from the equilibrium point via a degenerate Hopf bifurcation for a piecewise smooth Kolmogorov system of degree n. Specifically, we shot that MpKc(2)≥1, MpKc(3)≥12, and MpKc(4)≥18. In particular, we show at least one crossing limit cycle in Palomba's economics model, considering it from a piecewise smooth point of view. To our knowledge, these are the best quotes of limit cycles for piecewise smooth polynomial Kolmogorov systems in the literature.
Keywords: Center-focus; Cyclicity; Kolmogorov systems; Limit cycles; Lotka–Volterra systems; Lyapunov quantities; Weak-focus order